2016
DOI: 10.2174/1874325001610010241
|View full text |Cite
|
Sign up to set email alerts
|

Particle Disease: A Current Review of the Biological Mechanisms in Periprosthetic Osteolysis After Hip Arthroplasty

Abstract: Background:Inflammatory responses to wear debris cause osteolysis that leads to aseptic prosthesis loosening and hip arthroplasty failure. Although osteolysis is usually associated with aseptic loosening, it is rarely seen around stable implants. Aseptic implant loosening is a simple radiologic phenomenon, but a complex immunological process. Particulate debris produced by implants most commonly causes osteolysis, and this is called particle-associated periprosthetic osteolysis (PPO).Objective:The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…As expected, the presence of Ti particles induced profound changes in calvarial bone of both OVX and Sham‐OVX mice, which was consistent with previous studies . Previous research showed that the chronic inflammatory response to wear particles involving macrophages, osteoclasts and osteoblasts plays a pivotal role in the initiation and development of aseptic loosening . Macrophages produce more proinflammatory cytokines (TNF‐α, IL‐6, IL‐1β, and RANKL) after Ti particle stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, the presence of Ti particles induced profound changes in calvarial bone of both OVX and Sham‐OVX mice, which was consistent with previous studies . Previous research showed that the chronic inflammatory response to wear particles involving macrophages, osteoclasts and osteoblasts plays a pivotal role in the initiation and development of aseptic loosening . Macrophages produce more proinflammatory cytokines (TNF‐α, IL‐6, IL‐1β, and RANKL) after Ti particle stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…Hip arthroplasty procedures are a common treatment for advanced osteoarthritis and may result in a number of commonly encountered complications, such as loss of bone tissue and loosening of the implant . Magnetic resonance imaging is one of the preferred diagnostic tools to interrogate the complications, although practical challenges still remain .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] This complication is a macrophage-based inammatory response to wear particles generated regionally at implant interfaces, and the lifetime of a joint prosthesis has been convincingly shown to depend on the type and amount of implant debris. [6][7][8] The effect of wear particles on periprosthetic osteolysis is mainly associated with the dose, size, shape, and type of wear particle. [9][10][11][12] It is generally recognized that only particles of <10 mm in diameter induce an inammatory response in vitro.…”
Section: Introductionmentioning
confidence: 99%